PERCEPTION OF THE ARTISTIC FEATURES OF THE CHRONICLE NOVEL BY M.E. SALTYKOV-SHCHEDRIN "GENTLEMEN GOLOVLEVS" BY PHILOLOGY STUDENTS - Fazliddinov Shuxrat Faxriddinovich (International Journal of Innovations in Engineering Research and Technology, 2022)
The article discusses the perception of the artistic features of the novel-chronicle "Gentlemen Golovlevs" by M. E. Saltykov-Shchedrin. Psychological and pedagogical ways of analyzing the novel.